PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP DEPOT AIR MINUM DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI KOTA PEKANBARU - Alya Ramadhani Ridarto; Maryati Bachtiar; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law 8 of 1999 on Consumer Protection has guaranteed legal certainty toprotect consumers. This research is related to legal protection for consumersagainst drinking water depots in Pekanbaru City. The development of drinkingwater depots has an impact on consumer concerns. Therefore, it is necessary tostudy first, legal protection for consumers of drinking water depots in PekanbaruCity, second, factors inhibiting legal protection for consumers of drinking waterdepots in Pekanbaru City.This research is sociological legal research, because it is based on fieldresearch by collecting data from interviews, questionnaires and literature studiesthat have a relationship with problems that use qualitative data analysis so as toproduce descriptive data and are concluded with deductive thinking methods.From the results of the study, it was concluded that, first, legal protectionfor consumers of drinking water depots in Pekanbaru city has not been maximizedas expected by the Consumer Protection Law Number 8 of 1999. Second, theinhibiting factors of consumer protection itself are due to consumers lack ofknowledge of their rights that have been regulated in the UUPK, lack ofawareness of business actors to maintain the cleanliness and quality of theirdrinking water, as well as the absence of authority of the Pekanbaru City HealthOffice and the Pekanbaru City Industry and Trade Office to follow up on drinkingwater depots that are not in accordance with applicable laws and regulations.Keywords: Consumer Protection-Drinking Water Depots-Inhibiting Factors.